2012
DOI: 10.1242/jcs.090639
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic engineering: histone H3K9 acetylation is compatible with kinetochore structure and function

Abstract: SummaryHuman kinetochores are transcriptionally active, producing very low levels of transcripts of the underlying alpha-satellite DNA. However, it is not known whether kinetochores can tolerate acetylated chromatin and the levels of transcription that are characteristic of housekeeping genes, or whether kinetochore-associated 'centrochromatin', despite being transcribed at a low level, is essentially a form of repressive chromatin. Here, we have engineered two types of acetylated chromatin within the centrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
91
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 54 publications
6
91
0
Order By: Relevance
“…Epigenetic modifications of engineered human artificial chromosomes (HACs) confirmed the need for a critical balance in transcription levels for properly functioning centromeres (Bergmann et al 2011(Bergmann et al , 2012 and reviewed in this issue). These studies also showed that active transcription, not histone modifications, is a key element to maintaining centromere function.…”
Section: Centromeric Transcriptionmentioning
confidence: 93%
See 4 more Smart Citations
“…Epigenetic modifications of engineered human artificial chromosomes (HACs) confirmed the need for a critical balance in transcription levels for properly functioning centromeres (Bergmann et al 2011(Bergmann et al , 2012 and reviewed in this issue). These studies also showed that active transcription, not histone modifications, is a key element to maintaining centromere function.…”
Section: Centromeric Transcriptionmentioning
confidence: 93%
“…1d). Alteration of the HAC centrochromatin to an open chromatin state likewise resulted in disrupted CENP-A loading; the altered chromatin state did not directly affect the HAC's centromere activity, rather the resulting increase in transcription lead to the observed detrimental effects (Bergmann et al 2012) (Fig. 1d).…”
Section: Centromeric Transcriptionmentioning
confidence: 97%
See 3 more Smart Citations